2014
DOI: 10.1039/c4ra05591h
|View full text |Cite
|
Sign up to set email alerts
|

Source and major species of CHx(x = 1–3) in acetic acid synthesis from methane–syngas on Rh catalyst: a theoretical study

Abstract: Density functional calculations have been carried out to investigate the source and major species of CH x (x ¼ 1-3) involved in acetic acid synthesis from methane-syngas on the Rh(111) surface. All possible formation pathways of CH x (x ¼ 1-3) from methane and syngas have been systematically investigated. For CH x formation from methane, our results show that CH is the most abundant species; for CH x formation from syngas, all CH x (x ¼ 1-3) species form from CHO by CO hydrogenation, and the optimal formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The metal Rh has been known as a promising element toward the formation of ethanol from CO hydrogenation. ,,, The Rh catalyst with FCC crystal phase structure has been studied widely in both experiment and theory. The experimentally prepared Rh-based catalysts with FCC crystal phase exhibit a high selectivity of C 2+ oxygenates but a low CO conversion. , Numerous DFT studies have been focused on CO dissociation on FCC Rh surfaces. The results showed that the H-assisted pathway through CHO is the underlying activation way on Rh surfaces, and the studies also indicated that the stepped surfaces have higher activity than the flat surfaces. However, CO dissociation on HCP Rh has rarely been studied, although the other metal nanoparticle with HCP crystal phase was reported to show different catalytic properties compared to FCC crystal phase. Recent studies by Huang et al have successfully synthesized HCP Rh crystal phase by the experimental technology for the first time. As a result, the metal Rh can exist in the form of HCP and FCC crystal phase.…”
Section: Introductionmentioning
confidence: 99%
“…The metal Rh has been known as a promising element toward the formation of ethanol from CO hydrogenation. ,,, The Rh catalyst with FCC crystal phase structure has been studied widely in both experiment and theory. The experimentally prepared Rh-based catalysts with FCC crystal phase exhibit a high selectivity of C 2+ oxygenates but a low CO conversion. , Numerous DFT studies have been focused on CO dissociation on FCC Rh surfaces. The results showed that the H-assisted pathway through CHO is the underlying activation way on Rh surfaces, and the studies also indicated that the stepped surfaces have higher activity than the flat surfaces. However, CO dissociation on HCP Rh has rarely been studied, although the other metal nanoparticle with HCP crystal phase was reported to show different catalytic properties compared to FCC crystal phase. Recent studies by Huang et al have successfully synthesized HCP Rh crystal phase by the experimental technology for the first time. As a result, the metal Rh can exist in the form of HCP and FCC crystal phase.…”
Section: Introductionmentioning
confidence: 99%
“…We previously synthesized TiO 2 NR using a low temperature hydrothermal method at normal pressure, employing NaF or KBr as shape control agent. [ 24,32 ] In this study, we introduced the Ag precursors into the system to enable in situ formation of Ag nanoparticles that can tightly adhere to the surfaces of TiO 2 nanorods during refluxing at 100 °C. The SEM and TEM images of the TiO 2 NR–Ag composite nanoparticles and pure TiO 2 NR were shown in Figure , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In order to estimate the selectivity of the major production of CH 4 and CH 3 OH on Ga 3 Ni 5 (111) surface, microkinetic modeling has been used to calculate the reaction rate of the major production and the overall reaction rate under experimental conditions (1 atm, CO 2 :H = 1:3, T = 500–600 K). The detailed information about microkinetic modeling is given in section 3 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%